Coal and sewage sludge ashes as sources of rare earth elements. (15th March 2017) - Folgueras, M.B.; Alonso, M.; Fernández, F.J.
Highlights: REY distributions in ashes of a bituminous coal and three sewage sludges were studied. REY concentrations in sludge ashes are lower than in coal ashes, excepting for La. Correlations and associations between major and minor elements and REY were obtained. Abstract: Rare earth elements together with Y and Sc (REY) are essential in the development of technology for clean and efficient use of energy. Apart from the potential of coal and sewage sludge as energy resources, the enrichment of REY in their ashes may provide a feasible source of them. The concentrations of REY in ashes obtained at 800 and 1100 °C of a bituminous coal and three types of sewage sludge were determined. Also, their relationships with major and minor elements and minerals were studied. The concentrations of REY, excepting for La, are higher in the coal ashes than those of the sludge ashes. In both types of materials, REY are associated with the inorganic matter, although the associations are different for the coal than for the sludges. In the coal ashes, La, Ce, Pr and Nd are mainly associated with silicates and aluminosilicates in ashes at 800 and 1100 °C. The rest of REY (excepting Sm and Yb) are associated with carbonates in ashes at 800 °C and with sulphates in ashes at 1100 °C. In the sludge ashes, Y is associated with carbonates, while other REY are mainly associated with phosphates, silicates and aluminosilicates.